2010
DOI: 10.1093/nar/gkq076
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 null vertebrate cells exhibit altered nucleosome architecture

Abstract: In eukaryotic nuclei, DNA is wrapped around an octamer of core histones to form nucleosomes, and chromatin fibers are thought to be stabilized by linker histones of the H1 type. Higher eukaryotes express multiple variants of histone H1; chickens possess six H1 variants. Here, we generated and analyzed the phenotype of a complete deletion of histone H1 genes in chicken cells. The H1-null cells showed decreased global nucleosome spacing, expanded nuclear volumes, and increased chromosome aberration rates, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…However, LH is present at various lower levels in proliferating cells (31) and is not required for metaphase chromatin condensation (30,37). The above-cited studies are consistent with our finding that the pattern of internucleosomal interactions in metaphase chromosomes is typical of chromatin without LHs (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, LH is present at various lower levels in proliferating cells (31) and is not required for metaphase chromatin condensation (30,37). The above-cited studies are consistent with our finding that the pattern of internucleosomal interactions in metaphase chromosomes is typical of chromatin without LHs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The type of interactions at the range of <20 kb of DNA revealed by our EM-assisted nucleosome capture experiments and modeling suggest a global nucleosome array condensation mechanism: in mitosis, the loop size would be modulated by factors promoting frequency of loop formation along the chromosome axis such as condensin (30,37) as well as chromatin fiber flexibility and interdigitation such as decreased linker histone affinity (38), metaphase-specific histone modifications (42), and increased divalent cation association (43). Further experimental and modeling studies of nucleosome interactions using high-resolution multiscale computational approaches (2,44) are essential for connecting chromatin's structural and epigenetic states.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies in unicellular eukaryotes have shown the roles of H1 in development, transcriptional regulation and the recombination at rDNA locus [5961]. In contrast, high eukaryotes have multiple variants of linker histone H1, which function in nucleosome spacing in chicken cells [62] as well as in mouse cells and embryonic development in mice [63]. In Arabidopsis, histone H1 contributes to DNA methylation and gene imprinting [64,65].…”
Section: The Universality Of Histone Variantsmentioning
confidence: 99%
“…Simultaneous knockdown of three Arabidopsis H1 genes by RNAi results in developmental defects and DNA hypo or hypermethylation (Wierzbicki and Jerzmanowski, 2005). The histone H1 null chicken cells show decreased global nucleosome spacing, expanded nuclear volumes, and increased chromosome aberration rates, but maintain proper mitotic chromatin structure, suggesting roles of linker histone H1 in nucleosome spacing, interphase chromatin compaction and global regulation of transcription (Hashimoto et al, 2010). In mice, embryos without the three H1 subtypes (H1c, H1d, and H1e) and with 50% of the normal ratio of H1 to nucleosomes die by mid-gestation, suggesting that the total amount of H1 is crucial for proper embryonic development (Fan et al, 2003).…”
Section: Histone H1 Variantsmentioning
confidence: 99%